THE INFLUENCE OF SERVICE QUALITY AND TAX KNOWLEDGE ON THE COMPLIANCE LEVEL OF INDIVIDUAL TAXPAYERS AT THE DOMPU TAX SERVICE, COUNSELING AND CONSULTATION OFFICE (KP2KP) - M. Ikhwan Mansyuri; Fahrul Mauzu; Yuliana (International Journal of Social Science, 2022)
This research is a quantitative research with a case study at the Office of Tax Services, Extension and Consultation (KP2KP) Dompu. With the aim of knowing the effect of service quality and tax knowledge on the level of compliance of individual taxpayers. This study uses a sample of 100 individual taxpayer respondents with sampling using purposive sampling method. The method used in this research is Multiple Linear Regression Analysis. The results of this study indicate that service quality has a positive effect on the level of compliance of individual taxpayers and tax knowledge has a positive effect on the level of compliance of individual taxpayers. The value of Adjusted R Square for the coefficient of determination (R2) of 0.614 or 61.4% of the individual taxpayer compliance level is influenced by service quality and tax knowledge. The remaining 38.6% is influenced by other factors apart from service quality and tax knowledge.